EDUKASI SECARA DARING TENTANG PEMANFAATAN MOODLE UNTUK GURU DAN DOSEN SELAMA PANDEMI COVID-19 - Khoirul Rista Abidin; Puji Astuti; Zahro Mufida; Fadli Sukandiarsyah; Puspa Amalia (Politeknik 'Aisyiyah Pontianak, 2021)
Background Online learning is the implementing learning and teaching process that is carried out without face to face directly or by means of applications via the internet. Moodle is one of the learning applications that can be included. Purpose : This study is aimed to analyze the effect of online education on educators, namely teachers and lecturers, regarding the use of Moodle as a resource for distance learning during the Covid-19 pandemic. Methods: Moodle educational activities were conducted online for 2 days by inviting all educators from Sabang to Merauke. At the end of the activity, participants were evaluated by asking to fill in quiz questions to determine their level of understanding about Moodle. Results Participants who took part in the Moodle training activity were 763 people, consisting of teachers and lecturers with an educational background of S1, S2 and S3. The results of the evaluation are as many as 85% of subjects get a score of> 50. Conclusion Moodle can be a recommendation application to support innovative distance learning.